ВІЗУАЛЬНЕ МОДЕЛЮВАННЯ ОДНОФАЗНОГО МОСТОВОГО ВИПРЯМЛЯЧА - Алєксєєв, О.Г.; Алексієвський, Д.Г.; Туришев, К.О.; Шмалій, С.Л.; Панкова, О.О. (Інститут електродинаміки Національної академії наук України, 2018)
The question of construction and using thyristor single-phase bridge rectifier mathematical modeling visual modeling resources was describes in the article. The proposed mathematical model has higher performance then the circuit simulation. This permits to reduce modeling time of complex electrical system. It includes a thyristor single-phase bridge rectifier. The proposed mathematical model implementation describes its operation in continuous current model and an intermittent current model. The question of a model adequacy the proposed mathematical model was describes by comparison of modeling results. An investigation of the control angle influence on the magnitude of the error that occurs when simulating the rectifier-starting mode. References 6, figures 5.